Prerrogativa ou privilégio: uma análise do auxílio-moradia para juízes à luz dos princípios constitucionais da moralidade e da legalidade - Morais, Vitória Larissa Dantas de (Universidade Federal Rural do Semi-Árido, 2019)
This article has the purpose to analyse the concession of the housing assistance to brazilian judges, emphasizing the defermen of the injuction by the Eminent Minister of the Federal Supremme Court of Brasil, Luiz Fux, on 2014, until it’s revocation, in november of 2018. Until the year of 2014, each state of the Federation treated the housing assistance in a isoleted and different way. The same thing occourred to the Federal Justice. Based on the principle of the isonomy, the judges started to organize themselves, specifically on the Federal Justice, to provide the payment of the housing assistence to all brazilian federal judges. After the concession of the injuction, other judges classes also required the value, wich was also deferred. The decisions of the Supreme Court about the theme had reached big repercussion at the nacional media, attracting discussions in Society as well as at academic and juristic sphere. Among the arguments is the idemnification aspect of the housing assistance. It i salso questioned if the housing assistance could have been defered by the deferred by the judiciary, wich has been the beneficiary of the decision and it’s author. Besides, the housing assistance respected the constitutional principles of the legality and morality? To understand better the subject, the mentioned assistance will be studied since it’s emergence until the very recents regulations, so will also be possible to analyse the constitucional and infraconstitucional articles about it. Besides that, using the hypothetical-deductive method and a documental and bibliographic research, will also be discussed how brazilian jurisprudence has been dealing with the theme, analysing how the General Counsel of the Union and the General Attorney of the Republic are expressing their opinions about the housing assistance. After the exposure of the favorable and opposed arguments, they will be discussed together, in a way to reach the conclusion that the housing assistance payed to brazilian judges does not respect the constitutional principles of morality and legality, wich also can be defined as a truly privilegie of the mentioned category of public agents.
Artigo Acadêmico
Keywords: Auxílio-moradia; Legalidade; Moralidade; Juízes; Housing assistance; Morality; Legality; Judges; CIENCIAS SOCIAIS APLICADAS::DIREITO